Thermal Analysis in Pipe Flow: Influence of Variable Viscosity on Entropy Generation - Bekir Sami Yilbas (Entropy, 2004)
Abstract: Flow through pipes and heating situations find wide applications in industry. Depending on the fluid properties, temperature field in the pipe changes. This in turn results in thermodynamic irreversibility in the flow system. Thermodynamic irreversibility can be quantified through amount of entropy generation in the thermal system. Consequently, in the present study, the influence of fluid viscosity on the entropy generation due to pipe flow heated from the pipe wall at constant temperature is examined. The turbulent flow with conjugate heating situation is accommodated in the analysis. The governing equations of flow and heat transfer are solved numerically using a control volume approach. Entropy generation rate due to different pipe wall temperatures is computed. It is found that the volumetric entropy generation rate in the pipe is higher for variable properties case; however, total entropy generation rate in the pipe wall attains considerably lower values for variable viscosity case as compared to that corresponding to the constant viscosity case.